Limited Contract Enforcement and Strategic Renegotiation - Huberman, Gur; Kahn, Charles (American Economic Review, 1988)
This paper presents a strategic theory of contract renegotiation. In this theory, suboptimal contracts are put in place initially to protect one party against undesirable actions by another party and are renegotiated once the danger is past. We develop a model to establish the cases in which simple contracts cannot achieve desirable outcomes, so that only a complicated contract or renegotiation will serve. Unlike most previous accounts of contract renegotiation, this theory does not rely on exogenous uncertainty to motive renegotiation.